Poly (p-dioxanone) degradable melt-blown non-woven material as well as preparation method and application thereof
By optimizing the preparation process of polyptioxane, including limited viscosity and melt index, vacuum drying and precise temperature setting, the problem of product quality in the meltblown process is solved, and the preparation of high-performance polyptioxane degradable meltblown nonwoven materials is achieved, which is suitable for multiple application fields.
Patent Information
- Application Number
- CN202510085001.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-03-28
AI Technical Summary
When using polypti-dioxycyclohexanone as raw material for meltblown process production, there is a lack of clear process guidance and it is difficult to accurately control the parameters of each link, resulting in unstable product quality and large fluctuations in performance.
A set of preparation methods for polyp-dioxycyclohexanone degradable meltblown nonwoven materials is designed, including defining the viscosity and melt index of the slices, vacuum heating and drying, accurately setting the temperature of each section of the screw, and drawing the microfibers through spinnerets and airflow.
By optimizing process parameters, the stability and consistency of product performance is achieved, the excellent performance of polyoxycyclohexanone is fully utilized, and the product quality is improved. It is suitable for clinical medicine, sanitary materials, agriculture and food packaging fields.
Smart Images

Figure BDA0005249865600000221
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nonwoven materials, and in particular to a polydioxanone degradable melt-blown nonwoven material and a preparation method and application thereof. Background Art
[0002] The new biodegradable material polydioxanone (PPDO) is an aliphatic polyester-ether. The ester bond in its main molecular chain makes PPDO have excellent biodegradability. It can be gradually decomposed in the natural environment or in the body, effectively avoiding the continuous pressure on the environment caused by the long-term retention of traditional non-degradable materials, as well as the problem of foreign matter residues that may be caused in biomedical applications. At the same time, the excellent biocompatibility ensures that the material can coexist harmoniously when in contact with biological tissues, and will not cause harmful immune responses or adverse reactions such as inflammation, greatly improving its safety in the biomedical field. In addition, under specific physiological conditions, it can be absorbed by human tissues at a predetermined rate, without the need for secondary surgery to remove it, reducing the patient's pain and medical costs. The presence of ether bonds in its main molecular chain makes the polymer have good strength and excellent toughness. It has been used to prepare degradable surgical sutures and plays an important role in clinical medicine.
[0003] Meltblown nonwoven technology is a type of polymer direct web-forming method. It is a process in which the polymer melt extruded from a screw extruder is blown by a high-speed, high-temperature airflow to cause the melt to be extremely stretched to form ultrafine fibers, which are then gathered on a web curtain to form a fiber web. Finally, the fibers are reinforced by self-adhesion to form meltblown nonwoven materials. Meltblown nonwoven materials play a key role in medical protection (such as masks and protective clothing) and sanitary materials (such as sanitary napkins and diapers) because of their excellent barrier filtration and air permeability.
[0004] The melt-blown method for producing polydioxanone nonwoven materials has the characteristics of short process flow and high production efficiency. The polydioxanone nonwoven material products obtained not only retain the original advantages of ultrafine fibers, but also have biodegradability, biocompatibility, absorbability, excellent strength and toughness. They have great application potential in medical protection, sanitary materials, environmental protection (such as degradable filter materials in air filtration and water purification), agriculture (such as degradable plant covering materials, seed coating materials), and food packaging (degradable food preservation packaging materials).
[0005] Although meltblown nonwoven technology has many advantages, it faces unprecedented challenges when using polydioxanone as raw material for meltblown production. The production process of meltblown nonwoven materials covers multiple key links, such as feeding, screw melt extrusion, filtration, die spinning, high-temperature and high-speed airflow drawing to form ultrafine fibers, and bonding on the mesh curtain. However, to date, there is a serious lack of relevant information on the meltblown process using polydioxanone as raw material, which makes it difficult to accurately control the parameters of each link in the actual production process, resulting in unstable product quality and large performance fluctuations, and unable to give full play to the potential of polydioxanone in meltblown nonwoven materials.
[0006] Based on this, it is necessary to design a preparation method for polydioxanone melt-blown nonwoven materials that can give full play to the excellent performance of PPDO raw materials, while optimizing the melt-blown process, improving product quality and stability, and laying a solid foundation for the wide application of polydioxanone melt-blown nonwoven materials in the medical field and other related fields. Summary of the invention
[0007] The object of the present invention is to provide a polydioxanone degradable melt-blown nonwoven material that solves the above technical problems.
[0008] Another object of the present invention is to provide a method for preparing the above-mentioned polydioxanone degradable melt-blown nonwoven material.
[0009] Another object of the present invention is to provide an application of the polydioxanone degradable melt-blown nonwoven material.
[0010] To this end, the technical solution of the present invention is as follows:
[0011] A polydioxanone-degradable melt-blown nonwoven material is prepared from polydioxanone as a raw material. The polydioxanone is heated and melted by a twin-screw extruder, extruded from a spinneret, and stretched at high speed in a hot air flow to form fibers. The fibers are self-bonded into a web and collected by a receiving device to obtain a melt-blown nonwoven material.
[0012] The polydioxanone-degradable meltblown nonwoven material uses polydioxanone (PPDO) as the key raw material and has a unique molecular structure. The ester bond in the main chain of the molecule is the key factor that gives the material excellent biodegradability, allowing the material to gradually decompose according to a specific degradation mechanism in the natural environment or in the body, and can effectively avoid the environmental pressure caused by the long-term retention of traditional non-degradable materials and the problem of foreign matter residue that may be caused in biomedical applications. The presence of ether bonds in the molecular chain brings good strength and excellent toughness to the material. This combination of strength and toughness makes it difficult to break when subjected to external forces, and can meet the use requirements under a variety of complex working conditions.
[0013] In the first step of preparing the polydioxanone degradable melt-blown nonwoven material, the viscosity of the polydioxanone used for slicing is first strictly limited to 1.5 dL / g to 2 dL / g and a melt index of 20 g / 10 min to 25 g / 10 min; for the polydioxanone having the above performance parameters, its glass transition temperature range is generally -9°C to -11°C, and the melting temperature range is generally 97°C to 115°C. The above-mentioned limitation on the raw material performance parameters of polydioxanone is intended to ensure that the slices can be smoothly melted and plasticized in the subsequent processing process, and finally form a melt-blown nonwoven material with excellent performance; specifically, the appropriate viscosity range ensures the fluidity and processability of the material in the screw extruder, and the melt index affects the melting speed and molding performance of the material; the applicant has found through a large number of screening experiments that when the viscosity and melt index of polydioxanone are outside the appropriate range, the filament state of the prepared fiber obviously has problems such as uneven thickness and poor molding effect; and the glass transition temperature and melting temperature of polydioxanone are related to the processing temperature setting in the subsequent melt extrusion link, drawing environment and other steps, thereby realizing the preparation of melt-blown nonwoven materials based on materials with appropriate parameters.
[0014] Before the fiberization of the polydioxanone slice material, it is preferred to dry the material by vacuum heating and drying so that the slice reaches a suitable physical state and ensures the smooth progress of the subsequent melt extrusion process; specifically, the drying temperature is precisely controlled at 50°C to 70°C, and the drying time is 12h to 48h. The applicant has found through a large number of screening experiments that by using the above-defined temperature range and time range, the slice can fully remove the internal moisture while maintaining its inherent properties, avoiding defects such as bubbles caused by the vaporization of moisture during the high-temperature melting process, thereby affecting the mechanical properties of the material; among them, the vacuum drying environment helps to reduce the boiling point of moisture, accelerate the drying process, and improve production efficiency.
[0015] In the heating and melting stage, the melt extrusion process of the slices in the twin-screw extruder is one of the core links of the whole process, in which the precise setting of the temperature of each section of the screw is very important. The temperature of the first zone is set at 85°C to 95°C. In this temperature range, the slices begin to soften due to heat, laying the foundation for the subsequent melting process, while avoiding the premature melting of the slices due to excessive temperature and affecting the normal transportation of the material; the temperature of the second zone is set at 155°C to 165°C, which further promotes the melting of the slices and gradually transforms the material into a uniform melt state; and the temperatures of the third and fourth zones are both kept at 170°C to 180°C. The polymer melts in these two zones are fully plasticized under the high temperature and the shearing action of the screw to reach a highly uniform state, ensuring the quality and stable performance of the melt; the die temperature is set at 170°C to 180°C, and is preferably consistent with the set temperatures of the aforementioned third and fourth zones, so that the melt can maintain good fluidity and pressure distribution in the die, thereby being uniformly extruded from the spinneret to form a slender and uniform filamentary melt flow, providing good basic conditions for the subsequent airflow drawing process.
[0016] After a large number of screening experiments, the applicant found that whether the temperature setting range of each zone in the heating and melting stage conforms to the above-mentioned limited range has a significant impact on the performance of the final meltblown nonwoven material; specifically, when the temperature of one zone is set too low, the softening degree of the slice is insufficient, the fluidity of the material is poor, and the material is difficult to be smoothly transported forward under the push of the screw, resulting in accumulation of the material in one zone, resulting in uneven melting, and the final fiber thickness is uneven, affecting the mechanical properties of the product; and when the temperature of one zone is set too high, the slice will melt prematurely, the melt will gather locally and flow poorly, making the material transportation unstable, affecting the continuity of subsequent processing, and may also cause polymer degradation due to local overheating, reducing the molecular weight of the melt. , affecting the strength and toughness of the fiber; when the temperature of the second zone is set too low, the slices cannot be fully melted, and there will be more incompletely melted particles in the melt. These particles will cause nodules and uneven thickness of the fiber when they are subsequently extruded through the spinneret and airflow drawing; when the temperature of the second zone is set too high, the polymer may accelerate degradation due to overheating, the polymer molecular chain after degradation will break, the viscosity of the melt will change, and the tensile properties of the fiber will be affected during the subsequent airflow drawing, making it difficult to form uniform ultrafine fibers, and even fiber breakage may occur during the drawing process, resulting in a decrease in the strength and flexibility of the product; when the temperature of the third zone is set too low, the melt is not fully plasticized, and the internal molecular chains are arranged and distributed unevenly. This uneven melt cannot form a uniform fiber structure during extrusion and drawing, resulting in large differences in fiber diameter; when the temperature of the third zone is set too high, the polymer will undergo excessive thermal oxidation, which will not only change the chemical structure of the polymer, reduce the biodegradability of the material, but also produce some low-molecular volatiles. These volatiles form pores inside the fiber, affecting the density of the fiber, resulting in reduced strength of the material, and may also affect the material's air permeability and filtration performance; in terms of die temperature setting, if the die temperature is set too low, the viscosity of the melt increases, the fluidity deteriorates, resulting in uneven melt flow speed in the die, inconsistent extrusion pressure of the filament bundle when extruded from the spinneret, and uneven thickness of the formed filament bundle. If the die temperature is set too high, the melt may further degrade while staying in the die. At the same time, too high a temperature will cause the melt to be extruded from the spinneret before airflow stretching, resulting in paralleling and adhesion due to reduced viscosity, resulting in abnormal fiber morphology and the inability to form a uniform fiber web.
[0017] In the air flow drawing forming step, the filament bundle ejected from the spinneret enters the high-temperature and high-speed air flow drawing area, the air flow pressure is set at 0.1MPa~0.5MPa, and the air flow temperature is set at 160℃~180℃; specifically, air flow drawing is the key step in transforming the melt stream into ultrafine staple fibers, and the precise control of air flow pressure and temperature directly affects key indicators such as fiber diameter, orientation and mechanical properties; appropriate air flow pressure can provide sufficient stretching force to stretch the filament bundle into ultrafine staple fibers under the action of air flow, while the air flow temperature affects the viscosity and fluidity of the melt, thereby affecting the fiber forming process; by precisely adjusting the air flow pressure and temperature, ultrafine staple fibers with different performance characteristics can be prepared according to actual needs.
[0018] After a large number of screening experiments, the applicant found that in the airflow drawing molding step, too large an aspect ratio will cause uneven fiber distribution, while too small an aspect ratio will cause large differences in the thickness of the filament bundles; too large an airflow pressure will cause the fiber diameter to be too thin and unevenly distributed, and easy to break, while too small an airflow pressure will cause the fiber diameter to be coarse; in addition, in this step, too high a temperature will cause a significant decrease in the viscosity of the polymer melt, the fiber is prone to over-stretching, and may also induce thermal decomposition or thermal oxidation reaction of the polymer; too low a temperature will cause incomplete fiber stretching, coarse and uneven fiber diameter, and reduce product strength and flexibility.
[0019] In summary, the settings of the various parameters in the above-mentioned multiple preparation steps of the polydioxanone degradable melt-blown nonwoven material do not exist in isolation, but are mutually coordinated and mutually influential; the reasonable distribution of the temperature of each section of the screw is closely related to the fluidity and plasticization degree of the melt, which in turn affects the pressure stability and extrusion uniformity of the melt during the spinning process; the pressure and temperature of the air drafting need to match the spinning parameters to ensure that the filaments extruded from the spinneret can be stretched into ideal ultra-fine short fibers under appropriate conditions. Through in-depth research and optimized combination of these process parameters, the efficient and stable operation of the entire preparation process is achieved, ensuring the consistency and reliability of product performance.
[0020] In the field of clinical medicine, the polydioxanone biodegradable melt-blown nonwoven material is used as a material for surgical dressings, wound dressings, masks, and protective clothing; in the field of sanitary materials, it is used as a material for sanitary napkins, diapers, and wet wipes.
[0021] The polydioxanone degradable melt-blown nonwoven material is used in the agricultural field as a material for making plant covering cloth and seed coating. The material can provide functions such as heat preservation, moisture retention, and weed prevention in the early stage of crop growth, and naturally degrade in the later stage of crop growth without the need for manual cleaning, thereby reducing agricultural production costs and environmental pollution.
[0022] The polydioxanone degradable melt-blown nonwoven material is used as a material for making food fresh-keeping packaging in the field of food packaging; the material can effectively extend the shelf life of food and can be naturally degraded after being discarded, solving the white pollution problem caused by traditional plastic packaging.
[0023] In addition, the preparation process of the present invention is relatively simple, starting from the drying of the slices, through a series of continuous processing steps, and finally directly making the melt-blown nonwoven material without complicated intermediate links or additional processing steps. This simple process not only reduces the energy consumption and equipment investment in the production process, but also reduces the unstable factors of product quality caused by complex processes. At the same time, the high production efficiency enables the material to be mass-produced in a shorter period of time, meeting the market's growing demand for high-performance, environmentally friendly nonwoven materials, and has good economic benefits and market competitiveness.
[0024] Compared with the prior art, the polydioxanone-degradable melt-blown nonwoven material uses polydioxanone as a raw material, is heated and melted by a twin-screw extruder, extruded from a spinneret, and formed by high-speed drawing in a hot air flow. It has good performance effects in mechanical strength (including tensile strength and flexibility), biodegradability (absorbability), filtration performance, air permeability, moisture resistance and chemical stability, so that it can be widely used in surgical dressings, wound dressing materials, mask materials, protective clothing materials in the field of clinical medicine, sanitary napkin materials, diaper materials, wet wipes materials in the field of sanitary materials, plant covering materials and seed coating materials in the field of agriculture, and food preservation packaging materials in the field of food packaging. DETAILED DESCRIPTION
[0025] The present invention will be further described below in conjunction with specific examples, but the following examples are by no means intended to limit the present invention in any way.
[0026] Example 1
[0027] A polydioxanone degradable melt-blown nonwoven material is prepared by the following method:
[0028] S1. Take a slice of polydioxanone, the viscosity of which is 1.5 dL / g, the melt index is 25 g / 10 min, the glass transition temperature is -9°C, and the melting temperature is 97°C; vacuum heat the slice to dry it at a drying temperature of 50°C and a drying time of 12 h;
[0029] S2, the dried slices are fed into a twin-screw extruder, and the temperature of the twin-screw extruder is set to 85°C in zone 1, 155°C in zone 2, 170°C in zone 3, 170°C in zone 4, and 170°C in the die head;
[0030] S3. After heating and melting, the fibers are extruded through a spinneret with an aspect ratio of 13:1. The molten stream extruded from the spinneret is drawn by an air flow at a temperature of 160°C and a pressure of 0.1 MPa to form ultrafine short fibers, which are self-bonded into a web and collected by a receiving device to obtain a meltblown nonwoven material.
[0031] Example 2
[0032] A polydioxanone degradable melt-blown nonwoven material is prepared by the following method:
[0033] S1. Take slices of polydioxanone, with a viscosity of 1.8 dL / g, a melt index of 22 g / 10 min, a glass transition temperature of -10°C, and a melting temperature of 105°C; dry the slices by vacuum heating at a drying temperature of 60°C for 30 hours;
[0034] S2, the dried slices are fed into a twin-screw extruder, and the temperature of the twin-screw extruder is set to 90°C in zone 1, 160°C in zone 2, 175°C in zones 3 and 4, and 175°C at the die head;
[0035] S3. After heating and melting, the fibers are extruded through a spinneret with an aspect ratio of 15:1. The molten stream extruded from the spinneret is drawn by an air flow at a temperature of 170°C and a pressure of 0.3 MPa to form ultrafine short fibers, which are self-bonded into a web and collected by a receiving device to obtain a meltblown nonwoven material.
[0036] Example 3
[0037] A polydioxanone degradable melt-blown nonwoven material is prepared by the following method:
[0038] S1. Take a slice of polydioxanone with a viscosity of 2 dL / g, a melt index of 20 g / 10 min, a glass transition temperature of -11°C, and a melting temperature of 115°C; dry the slice by vacuum heating at a drying temperature of 70°C for 48 hours;
[0039] S2, the temperature of screw zone 1 is set to 95°C, the temperature of zone 2 is set to 165°C, the temperatures of zones 3 and 4 are both set to 180°C, and the die temperature is 180°C;
[0040] S3. After heating and melting, the melt is extruded through a spinneret with an aspect ratio of 20:1. The air flow pressure is increased to 0.5 MPa, and the air flow temperature is increased to 180°C. The melt stream is stretched into ultrafine short fibers, which are self-bonded into a web and collected by a receiving device to obtain a meltblown nonwoven material.
[0041] Example 4
[0042] A polydioxanone degradable melt-blown nonwoven material is prepared by the following method:
[0043] S1. Take slices of polydioxanone, with a viscosity of 1.6 dL / g, a melt index of 23 g / 10 min, a glass transition temperature of -10°C, and a melting temperature of 100°C; dry the slices by vacuum heating at a drying temperature of 55°C for 20 hours;
[0044] S2, screw zone 1 temperature is set to 88°C, zone 2 temperature is set to 158°C, zone 3 and zone 4 temperatures are both set to 172°C, and die head temperature is 172°C;
[0045] S3. After heating and melting, the melt is extruded through a spinneret with an aspect ratio of 12:1. The air flow pressure is increased to 0.2 MPa, and the air flow temperature is increased to 165°C. The melt stream is stretched into ultrafine short fibers, which are self-bonded into a web and collected by a receiving device to obtain a meltblown nonwoven material.
[0046] Example 5
[0047] A polydioxanone degradable melt-blown nonwoven material is prepared by the following method:
[0048] S1. Take slices of polydioxanone, with a viscosity of 1.9 dL / g, a melt index of 21 g / 10 min, a glass transition temperature of -10.5°C, and a melting temperature of 110°C; dry the slices by vacuum heating at a drying temperature of 65°C for 35 hours;
[0049] S2, screw zone 1 temperature 92°C, zone 2 temperature 162°C, zone 3 and zone 4 temperatures both 178°C, die head temperature 178°C;
[0050] S3. After heating and melting, the melt is extruded through a spinneret with an aspect ratio of 18:1. The air flow pressure is increased to 0.4 MPa, and the air flow temperature is increased to 175°C. The melt stream is stretched into ultrafine short fibers, which are self-bonded into a web and collected by a receiving device to obtain a meltblown nonwoven material.
[0051] Example 6
[0052] A polydioxanone degradable melt-blown nonwoven material is prepared by the following method:
[0053] S1. Take slices of polydioxanone, with a viscosity of 1.7 dL / g, a melt index of 24 g / 10 min, a glass transition temperature of -9.5°C, and a melting temperature of 103°C; vacuum heat dry the slices at a drying temperature of 60°C for 25 h;
[0054] S2, screw zone 1 temperature 90℃, zone 2 temperature 160℃, zone 3 and zone 4 temperature both 176℃, die head temperature 176℃;
[0055] S3. After heating and melting, the melt is extruded through a spinneret with an aspect ratio of 16:1. The air flow pressure is increased to 0.35 MPa, and the air flow temperature is increased to 172°C. The melt stream is stretched into ultrafine short fibers, which are self-bonded into a web and collected by a receiving device to obtain a meltblown nonwoven material.
[0056] Example 7
[0057] A polydioxanone degradable melt-blown nonwoven material is prepared by the following method:
[0058] S1. Take slices of polydioxanone, with a viscosity of 1.55 dL / g, a melt index of 24.5 g / 10 min, a glass transition temperature of -9.2°C, and a melting temperature of 98°C; dry the slices by vacuum heating at a drying temperature of 52°C for 15 hours;
[0059] S2, screw zone 1 temperature 86°C, zone 2 temperature 156°C, zone 3 and zone 4 temperatures are both 172°C, die head temperature 172°C;
[0060] S3. After heating and melting, the melt is extruded through a spinneret with an aspect ratio of 11:1. The air flow pressure is increased to 0.15 MPa, and the air flow temperature is increased to 162°C. The melt stream is stretched into ultrafine short fibers, which are self-bonded into a web and collected by a receiving device to obtain a meltblown nonwoven material.
[0061] Example 8
[0062] A polydioxanone degradable melt-blown nonwoven material is prepared by the following method:
[0063] S1. Take polydioxanone slices with a viscosity of 1.85 dL / g, a melt index of 21.5 g / 10 min, a glass transition temperature of -10.8°C, and a melting temperature of 112°C; vacuum heat dry the slices at a drying temperature of 68°C for 45 hours;
[0064] S2, screw zone 1 temperature 94°C, zone 2 temperature 164°C, zone 3 and zone 4 temperatures are both 176°C, die head temperature 176°C;
[0065] S3. After heating and melting, the melt is extruded through a spinneret with an aspect ratio of 19:1. The air flow pressure is increased to 0.45 MPa, and the air flow temperature is increased to 178°C. The melt stream is stretched into ultrafine short fibers, which are self-bonded into a web and collected by a receiving device to obtain a meltblown nonwoven material.
[0066] Example 9
[0067] A polydioxanone degradable melt-blown nonwoven material is prepared by the following method:
[0068] S1. Take polydioxanone slices with a viscosity of 1.95 dL / g, a melt index of 20.5 g / 10 min, a glass transition temperature of -10.5°C, and a melting temperature of 114°C; vacuum heat dry the slices at a drying temperature of 65°C for 38 hours;
[0069] S2, screw zone 1 temperature 93°C, zone 2 temperature 163°C, zone 3 and zone 4 temperatures are both 179°C, die head temperature 179°C;
[0070] S3. After heating and melting, the melt is extruded through a spinneret with an aspect ratio of 17:1. The air flow pressure is increased to 0.38 MPa, and the air flow temperature is increased to 175°C. The melt stream is stretched into ultrafine short fibers, which are self-bonded into a web and collected by a receiving device to obtain a meltblown nonwoven material.
[0071] Comparative Example 1
[0072] A polydioxanone degradable melt-blown nonwoven material is prepared by the following method:
[0073] S1. Prepare polydioxanone slices with a viscosity of 1 dL / g, a melt index of 25 g / 10 min, a glass transition temperature of -9°C, and a melting temperature of 97°C; vacuum heat dry the slices at a drying temperature of 50°C and a drying time of 12 h;
[0074] S2, putting the dried slices into a twin-screw extruder, and setting the temperature of the twin-screw extruder to 85°C in zone 1, 155°C in zone 2, 170°C in zone 3, 170°C in zone 4, and 170°C in die head;
[0075] S3. After heating and melting, it is extruded through a spinneret with an aspect ratio of 10:1, and drawn by an air flow at a temperature of 160°C and a pressure of 0.1 MPa.
[0076] Comparative Example 2
[0077] A polydioxanone degradable melt-blown nonwoven material is prepared by the following method:
[0078] S1. Prepare polydioxanone slices with a viscosity of 2 dL / g, a melt index of 15 g / 10 min (lower than the specified range), a glass transition temperature of -9°C, and a melting temperature of 97°C; vacuum heat dry the slices at a drying temperature of 50°C and a drying time of 12 h;
[0079] S2, putting the dried slices into a twin-screw extruder, and setting the temperature of the twin-screw extruder to 85°C in zone 1, 155°C in zone 2, 170°C in zone 3, 170°C in zone 4, and 170°C in die head;
[0080] S3. After heating and melting, it is extruded through a spinneret with an aspect ratio of 13:1, and stretched by an air flow at a temperature of 160°C and a pressure of 0.1 MPa.
[0081] Comparative Example 3
[0082] A polydioxanone degradable melt-blown nonwoven material is prepared by the following method:
[0083] S1. Take slices of polydioxanone, with a viscosity of 1.5 dL / g, a melt index of 25 g / 10 min, a glass transition temperature of -9°C, and a melting temperature of 97°C; vacuum heat dry the slices at a drying temperature of 40°C for 12 h;
[0084] S2. The dried slices are put into a twin-screw extruder, and the temperature of the twin-screw extruder is set to 85°C in zone 1, 155°C in zone 2, 170°C in zone 3, 170°C in zone 4, and 170°C in die head;
[0085] S3. After heating and melting, it is extruded through a spinneret with an aspect ratio of 13:1, and is drawn by air flow at a temperature of 160°C and a pressure of 0.1MPa to form ultrafine short fibers, which are then self-bonded into a web and collected by a receiving device.
[0086] Comparative Example 4
[0087] A polydioxanone degradable melt-blown nonwoven material is prepared by the following method:
[0088] S1. Take a slice of polydioxanone with a viscosity of 1.5 dL / g, a melt index of 25 g / 10 min, a glass transition temperature of -9°C, and a melting temperature of 97°C; vacuum heat dry the slice at a drying temperature of 50°C for 12 hours;
[0089] S2, the dried slices are fed into a twin-screw extruder, and the temperature of the twin-screw extruder is set to 85°C in zone 1, 155°C in zone 2, 170°C in zone 3, 170°C in zone 4, and 170°C in die head;
[0090] S3. After heating and melting, it is extruded through a spinneret with an aspect ratio of 13:1, and drawn by an air flow at a temperature of 150°C and a pressure of 0.1MPa.
[0091] Comparative Example 5
[0092] A polydioxanone degradable melt-blown nonwoven material is prepared by the following method:
[0093] S1. Take a slice of polydioxanone with a viscosity of 1.5 dL / g, a melt index of 25 g / 10 min, a glass transition temperature of -9°C, and a melting temperature of 97°C; vacuum heat dry the slice at a drying temperature of 50°C for 12 hours;
[0094] S2. The dried slices are put into a twin-screw extruder, and the temperature of the twin-screw extruder is set to 85°C in zone 1, 155°C in zone 2, 170°C in zone 3, 170°C in zone 4, and 170°C in die head;
[0095] S3. After heating and melting, it is extruded through a spinneret with an aspect ratio of 13:1, and stretched by an air flow with a temperature of 160°C and a pressure of 0.05MPa.
[0096] Comparative Example 6
[0097] A polydioxanone degradable melt-blown nonwoven material is prepared by the following method:
[0098] S1. Take a slice of polydioxanone with a viscosity of 1.5 dL / g, a melt index of 25 g / 10 min, a glass transition temperature of -9°C, and a melting temperature of 97°C; vacuum heat dry the slice at a drying temperature of 50°C for 12 hours;
[0099] S2. The dried slices are put into a twin-screw extruder, and the temperature of the twin-screw extruder is set to 100°C in zone 1, 155°C in zone 2, 170°C in zone 3, 170°C in zone 4, and 170°C in die head;
[0100] S3. After heating and melting, it is extruded through a spinneret with an aspect ratio of 13:1, and stretched by an air flow at a temperature of 160°C and a pressure of 0.1 MPa.
[0101] Comparative Example 7
[0102] A polydioxanone degradable melt-blown nonwoven material is prepared by the following method:
[0103] S1. Take a slice of polydioxanone with a viscosity of 1.5 dL / g, a melt index of 25 g / 10 min, a glass transition temperature of -9°C, and a melting temperature of 97°C; vacuum heat dry the slice at a drying temperature of 50°C for 12 hours;
[0104] S2, the dried slices are fed into a twin-screw extruder, and the temperature of the twin-screw extruder is set to 85°C in zone 1, 155°C in zone 2, 170°C in zone 3, 170°C in zone 4, and 170°C in die head;
[0105] S3. After heating and melting, it is extruded through a spinneret with an aspect ratio of 5:1, and drawn by an air flow at a temperature of 160°C and a pressure of 0.1 MPa.
[0106] Performance Test:
[0107] (I) Microstructure test:
[0108] Scanning electron microscope images of the meltblown nonwoven materials prepared in Examples 1 to 9 were collected to determine the fiber diameter of the materials; the fiber diameter results of each example are shown in Table 1 below.
[0109] Table 1:
[0110] Test Case Fiber diameter (μm) Example 1 2.5~4.5 Example 2 3.5~5.0 Example 3 4.0~6.0 Example 4 2.0~3.5 Example 5 5.0~7.0 Example 6 3.0~5.0 Example 7 2.0~4.0 Example 8 3.5~5.5 Example 9 2.5~3.5
[0111] It can be seen from Table 1 that the fiber diameter of the polydioxanone meltblown nonwoven material prepared in Examples 1 to 9 ranges from 2.0 μm to 7.0 μm, and the fiber diameter has a significant impact on the material properties in many aspects. Generally, finer fibers can form a denser structure, which significantly improves the filtration performance of the material. When filtering tiny particles, the pores between the fine fibers are smaller and more evenly distributed, which can effectively intercept smaller particles; and, it can be seen from Table 1 that the fiber diameter of each material is evenly distributed, and the diameter difference between fibers of different diameters does not exceed 2 mm, which is crucial to the stability of the material performance. The uniform fiber diameter distribution means that the internal structure of the material is uniform, so that the material can show better stability and reliability in terms of mechanical properties. However, due to their structural characteristics, fine fibers are relatively weak in air permeability. When air passes through materials composed of fine fibers, it needs to pass through narrower and more tortuous channels, which increases the resistance to air circulation and reduces the air permeability. On the contrary, materials with coarser fiber diameters have a relatively loose structure, larger gaps between fibers, and air is easier to circulate, so they have higher air permeability. Therefore, the appropriate fiber diameter can balance the effects of fiber diameter and the pores between fibers on the performance of meltblown nonwoven materials.
[0112] In addition, there are obvious differences in fiber diameters between the polydioxanone melt-blown nonwoven materials prepared in each embodiment, that is, by adjusting the process parameters in the preparation process, polydioxanone melt-blown nonwoven materials with different specified fiber distribution characteristics can be obtained; specifically, in addition to factors such as the viscosity of the raw material, the melt index, and the temperature settings of each area of the twin-screw extruder, which will affect the fluidity and processability of the melt and thus affect the forming of the fiber, the spinneret aspect ratio and the airflow drawing parameters also play a key role in the fiber diameter. For example, a larger spinneret aspect ratio and appropriate airflow drawing pressure and temperature contribute to the refinement of the melt stream, and finer fibers can be obtained.
[0113] Compared with Example 1, Comparative Example 1 is prepared by using polydioxanone chips with too low viscosity, and the fiber diameter range of the corresponding polydioxanone melt-blown nonwoven material is 2.0 μm to 8.0 μm, and the fiber diameter is relatively different from that of Example 1, that is, the uniformity of the fiber web is deteriorated; the reason is that the low-viscosity melt is easier to be stretched into fine fibers, but because it is too "soft", it is difficult to maintain a stable shape during the stretching process, and it is easy to have local over-stretching or under-stretching, so that the fiber diameters are different and the uniformity of the fiber web is deteriorated. In another comparative experiment, when polydioxanone chips with too high viscosity are used, the fluidity of the melt in the screw extruder is too poor during the processing process, and the material transportation is difficult. The extruded filament bundles are also uneven in thickness, and the fiber diameters of the corresponding melt-blown nonwoven material are greatly different and the overall thickness is relatively thick, which also affects the performance of the melt-blown nonwoven material.
[0114] Compared with Example 1, Comparative Example 2 is prepared by using polydioxanone chips with too low a melt index. During the processing, due to the low melt index, the melt is difficult to be stretched and refined. During the extrusion process, part of the melt cannot be smoothly extruded and then blocks the spinneret hole, resulting in the inability to form the fiber and the inability to prepare the melt-blown nonwoven material. In another comparative experiment, when polydioxanone chips with too high a melt index are used, the melt flows too fast during the extrusion process, making it difficult to accurately control the molding process, resulting in uneven fiber thickness and easy fiber breakage, which also affects the performance of the melt-blown nonwoven material.
[0115] Compared with Example 1, the fiber diameter of the polydioxanone melt-blown nonwoven material prepared in Comparative Example 4 is in the range of 5.0 μm to 7.0 μm, and its fiber diameter is significantly larger than that in Example 1. The reason is that the air flow temperature is set too low in the air flow drawing step of the comparative example, resulting in an increase in melt viscosity, poor fluidity, and difficulty in fully drawing the filament bundle into ultrafine short fibers. The actual fiber diameter formed is relatively thick and uneven. In another comparative experiment, if the air flow temperature is set too high in the air flow drawing step, the melt viscosity will drop sharply, the stability of the filament bundle will deteriorate during the drawing process, and problems such as paralleling and adhesion will easily occur, resulting in uneven diameter of the actually formed fibers and some fibers being too thin, thereby affecting the overall performance of the nonwoven material.
[0116] Compared with Example 1, the fiber diameter of the polydioxanone melt-blown nonwoven material prepared in Comparative Example 5 is in the range of 5.5 μm to 7.5 μm, and its fiber diameter is significantly larger than that in Example 1; the reason is that the airflow pressure in the airflow drawing step of this comparative example is insufficient, resulting in insufficient tensile force of the filament bundle, and the formed fiber diameter is relatively thick. In other comparative experiments, if the airflow pressure is set too high in the airflow drawing step, the tensile force on the filament bundle is too high, which will cause the fiber to be overstretched or even broken, and the formed fiber diameter is too thin and unevenly distributed, affecting the mechanical properties and quality stability of the nonwoven material.
[0117] Compared with Example 1, in the polydioxanone melt-blown nonwoven material prepared in Comparative Example 6, some fibers have a diameter less than 2 μm, and some have a diameter greater than 10 μm. The reason is considered to be that the temperature in one zone is too high, the slices melt and adhere to the screw too early, the material is not transported smoothly, and the extruded melt is uneven, resulting in a large difference in fiber diameter. This fiber diameter distribution makes the internal structure of the material chaotic, and it is impossible to form a tight and uniform fiber web, which seriously affects the microstructure of the material and thus affects the overall performance.
[0118] Compared with Example 1, the fiber diameter range of the polydioxanone melt-blown nonwoven material prepared in Comparative Example 7 is 6.5 μm to 8.5 μm, and its fiber diameter is significantly larger than that in Example 1. The reason is considered to be that the aspect ratio of the spinneret in the airflow drawing step of this comparative example is set too small, resulting in uneven shearing of the melt when it is extruded from the spinneret, large differences in the thickness of the formed filament bundles, and it is difficult to form ultrafine short fibers during the airflow drawing process, resulting in uneven fiber distribution of the nonwoven material.
[0119] (II) Mechanical properties test:
[0120] The mechanical properties of the meltblown nonwoven materials prepared in Examples 1 to 9 were tested, and the specific test results are shown in Table 2 below.
[0121] Table 2:
[0122] Test Case Tensile strength(MPa) Elongation at break (%) Example 1 9.5 205 Example 2 12.8 185 Example 3 14.5 155 Example 4 8.2 225 Example 5 15.8 125 Example 6 10.8 192 Example 7 6.8 230 Example 8 12.2 168 Example 9 7.5 215
[0123] From the results in Table 2, it can be seen that the tensile strength of the melt-blown nonwoven materials prepared by Examples 1 to 9 is between 6.8 MPa and 15.8 MPa, and the elongation at break is between 125% and 230%, indicating that the materials have both good strength and flexibility; Among them, the mechanical matching of the melt-blown nonwoven material prepared in Example 3 is good, and the reason for this is that the good matching of the raw material viscosity and the melt index with the processing temperature makes the fiber well formed and the molecular chains arranged closely; and the elongation at break test structure of the melt-blown nonwoven materials prepared in Examples 1 and 7 is better than the tensile strength test result, has better flexibility, and can withstand large deformation. The reason for this is that the raw material viscosity is low and the fiber molding is not tight enough during the processing.
[0124] Compared with Example 1, the tensile strength of the meltblown nonwoven material prepared in Comparative Example 1 is 5.5 MPa, and the elongation at break is 150%, which are significantly lower than those in Example 1. The reason is considered to be: referring to the microstructure test results of the comparative example, the fiber diameter bundles formed in the processing of the comparative example are uneven in thickness, resulting in uneven stress distribution inside the material. Under the action of external force, the thin parts are prone to break first, which leads to a decrease in the overall material strength, resulting in the mechanical strength of the meltblown nonwoven material being unable to meet normal use requirements.
[0125] Compared with Example 1, the tensile strength of the meltblown nonwoven material prepared in Comparative Example 3 is 4.0 MPa, and the elongation at break is 130%, which are significantly lower than those in Example 1. The reason is considered to be that before the screw melt extrusion step, the drying temperature is too low, resulting in insufficient removal of moisture in the slices. As a result, the moisture in the slices evaporates during the high-temperature melting process to produce a large number of bubbles, resulting in a loose internal structure of the formed fibers, a significant decrease in the strength of the nonwoven material, and the expected product performance standards cannot be achieved.
[0126] Compared with Example 1, the tensile strength of the meltblown nonwoven material prepared in Comparative Example 5 is 7.0_MPa, and the elongation at break is 140%, which is significantly lower than that in Example 1. The reason is that: although in general, the tensile strength may be better if the fiber diameter is thick, in Comparative Example 5, the fiber diameter is not only thicker, but also unevenly distributed, resulting in defects in the internal structure of the material. When subjected to stress, stress is concentrated on some of the coarser fibers, and there is a lack of close interweaving and support of sufficient fine fibers between the coarser fibers, which makes the stress transfer of the entire material uneven. At the same time, the number of coarse fibers accounts for a large proportion and is unreasonable in distribution, which limits the deformation ability of the material when subjected to stress, resulting in poor flexibility. In practical applications, this uneven structure is prone to problems such as breakage at the stress concentration point, which does not meet product quality standards.
[0127] Compared with Example 1, the tensile strength of the meltblown nonwoven material prepared in Comparative Example 7 is 6.0 MPa, and the elongation at break is 160%, which are significantly lower than those in Example 1. The reason is considered to be: referring to the microstructure test results of the comparative example, the fiber diameter bundles formed in the processing of the comparative example are uneven in thickness, resulting in uneven internal structure of the material, inconsistent deformation of various parts when subjected to force, resulting in stress concentration, resulting in poor mechanical properties, and unable to meet application requirements.
[0128] In practical applications, the tensile strength test results of the meltblown nonwoven material of the present invention can meet the requirements of the medical protection field for materials for making masks and protective clothing, and can withstand a certain amount of external force without being easily damaged; and the meltblown nonwoven material of the present invention has a high elongation at break, that is, the material has good deformability, so that it can adapt to different shape changes during use without breaking, and therefore can also be used in the field of sanitary materials for sanitary napkins, diapers and other products, and can naturally bend and stretch with the activities of the human body, providing a comfortable use experience.
[0129] (III) Degradation performance test:
[0130] The degradation performance of the meltblown nonwoven materials prepared by Examples 1 to 9 were tested, including degradation performance tests in a simulated soil environment (pH = 6.5-7.5, agricultural topsoil with a water content of 20% to 25%) and degradation performance tests in a simulated human tissue fluid environment (37° C., pH = 7.4 phosphate buffer solution); the specific test results are shown in Table 3 below.
[0131] Table 3:
[0132] Test Case Weight loss rate of soil environment materials (%) Tissue fluid environment material weight loss rate (%) Example 1 48 96 Example 2 42 92 Example 3 38 88 Example 4 60 99 Example 5 32 84 Example 6 45 94 Example 7 58 98 Example 8 36 90 Example 9 50 97
[0133] From the results in Table 3, it can be seen that the melt-blown nonwoven materials prepared by Examples 1 to 9 have a 6-month weight loss rate of 32% to 60% in a simulated soil environment; in a simulated human tissue fluid environment, the 6-month weight loss rate is between 84% and 99%; This shows that the material can achieve a certain degree of degradation in different environments, which is consistent with the degradation characteristics of polydioxanone; Under normal circumstances, melt-blown nonwoven materials with finer fiber diameters have a larger specific surface area, and the contact area with the degradation medium in the soil and tissue fluid environment increases accordingly, which is more conducive to the degradation reaction, and the degradation rate is relatively faster. Taking Example 4 and Example 7 as examples, the fiber of Example 4 is finer than that of Example 7, which makes the material of Example 4 have a larger specific surface area. In the simulated soil environment, the weight loss rate of Example 4 reaches 60%, which is higher than 58% of Example 7. In the simulated human tissue fluid environment, the weight loss rate of Example 4 is 99%, which is also slightly higher than 98% of Example 7, which is consistent with the law that the finer the fiber diameter, the more conducive to degradation.
[0134] In practical applications, the meltblown nonwoven material of the present invention can be degraded at an expected rate in both soil and human tissue fluid environments, effectively avoiding the pollution of ecological environments such as soil and water bodies caused by long-term accumulation of traditional non-degradable materials, conforming to the concept of sustainable development, and is particularly suitable for disposable medical and sanitary products; at the same time, the excellent biocompatibility of the material ensures that the material will not induce harmful immune responses or adverse reactions such as inflammation when in contact with biological tissues, greatly improving the safety of its application in the biomedical field, so that the material can be used in the field of medical protection. In addition to improving its application prospects as a material for making masks and protective clothing, it can also be used in direct contact with human tissues such as wound dressings and surgical dressings, such as surgical dressings and wound dressing materials. The biodegradable properties of this type of material in the human body enable it to be absorbed by human tissues at a predetermined rate without the need for secondary surgery to remove it, reducing the patient's pain and medical costs, and providing convenience for clinical medical applications.
[0135] In addition, the degradability of the meltblown nonwoven material of the present invention can also enable it to be applied to agriculture (such as degradable plant covering materials, seed coating materials), food packaging (degradable food preservation packaging materials) and other fields; specifically, in the agricultural field, the degradable plant covering materials can be naturally degraded in the later stage of crop growth, without the need for manual cleaning, reducing agricultural production costs and environmental pollution; in the field of food packaging, the degradable food preservation packaging materials can be naturally degraded after being discarded, solving the white pollution problem caused by traditional plastic packaging. This wide range of application fields provides a solid foundation for the market promotion and industrial development of materials, with significant social and economic benefits.
[0136] (IV) Filtration performance test:
[0137] The filtration performance of the meltblown nonwoven materials prepared in Examples 1 to 9 was tested, specifically, the filtration efficiency of the particles of 0.5 μm, 1 μm and 5 μm was tested, and the test results are shown in Table 4 below.
[0138] Table 4:
[0139] Test Case 0.5μm filtration efficiency (%) 1μm filtration efficiency (%) 5μm filtration efficiency (%) Example 1 94 96 99 Example 2 93 95 98 Example 3 91 93 97 Example 4 96 97 99.5 Example 5 90 94 96 Example 6 93.5 96.5 98.5 Example 7 95 97 99.8 Example 8 92 95 97.5 Example 9 93 95 99.2
[0140] From the results in Table 4, it can be seen that the melt-blown nonwoven materials prepared by Examples 1 to 9 have a filtration efficiency of 90% to 96% for 0.5 μm particles, 93% to 97% for 1 μm particles, and 96% to 99.8% for 5 μm particles. Compared with the filtration standards of melt-blown nonwoven materials generally used in medical protection and sanitation, the material exhibits a higher filtration efficiency for particles of different particle sizes. Generally, in the implementation standard GB 19083-2010 for medical protective masks, it is required that the filtration efficiency for 0.3 μm non-oily particles is not less than 95%. The filtration efficiency of the material of the present invention for 0.5 μm particles is close to or exceeds some existing product standards, and the filtration efficiency for 1 μm and 5 μm particles is even better, indicating that the melt-blown nonwoven material has good filtration performance, can effectively intercept various common tiny particles, and has significant advantages in filtration application scenarios.
[0141] Compared with Example 1, the polydioxanone melt-blown nonwoven material prepared in Comparative Example 4 has a filtration efficiency of 75% for 0.5 μm particles, 85% for 1 μm particles, and 90% for 5 μm particles, which are significantly lower than those in Example 1. The reason is considered to be: referring to the microstructure test results of the comparative example, the air flow temperature in the air flow drawing step of the comparative example is set too low, and the filament bundle is difficult to be fully drawn into ultrafine short fibers. The fiber diameter is coarse and uneven, resulting in the pores formed between the fibers being too large and unevenly distributed, making it easier for particles to penetrate the material, resulting in poor filtration performance of the nonwoven material and failure to meet application requirements.
[0142] In practical applications, the good filtering performance of the meltblown nonwoven material of the present invention further enhances its practicality in the above-mentioned medical and sanitary products, as well as medical protection products.
[0143] (V) Air permeability test:
[0144] The air permeability of the meltblown nonwoven materials prepared in Examples 1 to 9 was tested, and the specific test results are shown in Table 5 below.
[0145] Table 5:
[0146] Test Case Example 1 Example 2 Example 3 Example 4 Example 5 Air permeability 305mm / s 310mm / s 315mm / s 290mm / s 450mm / s Test Case Example 6 Example 7 Example 8 Example 9 Air permeability 320mm / s 300mm / s 330mm / s 335mm / s
[0147] From the results in Table 5, it can be seen that the air permeability of the meltblown nonwoven materials prepared by Examples 1 to 9 is between 290 mm / s and 450 mm / s. In the field of medical protection and sanitary products, air permeability is one of the important indicators for measuring the comfort and applicability of materials. For medical masks, if the air permeability is too high, it may not be able to effectively block tiny particles, bacteria and viruses in the air, reducing the protective effect; if the air permeability is too low, it will increase the breathing resistance of the wearer, produce a stuffy feeling, and reduce the comfort of wearing.
[0148] Generally speaking, the air permeability of common medical surgical masks is generally required to be no less than 240mm / s to balance the protective performance and wearing comfort. The air permeability of the meltblown nonwoven material prepared by the present invention is between 290mm / s and 450mm / s. This air permeability range can not only ensure that the material has a certain degree of protection, so that the internal fiber structure of the material can effectively intercept the tiny particles in the air, but also ensure that the air can pass through the material relatively smoothly, providing users with a more comfortable breathable experience. In the field of sanitary products, such as sanitary napkins, diapers, etc., suitable air permeability can keep the product dry, reduce the discomfort caused by moisture accumulation, and improve the user's satisfaction. Therefore, the air permeability of the meltblown nonwoven material of the present invention meets the requirements of medical protection and sanitary products for air permeability, and has good applicability in practical applications.
[0149] Among them, in the above embodiments, the meltblown nonwoven material with a finer fiber diameter (such as Example 4 and Example 7) has a relatively low air permeability due to its relatively dense fiber web structure, small gaps between fibers and more entanglements and bonding, and a tortuous and narrow air flow path. The air encounters great resistance when passing through. On the other hand, the meltblown nonwoven material with a coarser fiber diameter (such as Example 5) has a relatively loose fiber web structure, large gaps between fibers and is not easy to fit tightly to form larger pores, so air can pass through more easily.
[0150] Compared with Example 1, the meltblown nonwoven material prepared in Comparative Example 3 has insufficient moisture removal in the slices due to the low drying temperature. Therefore, the moisture is easily vaporized during the high-temperature melting process to produce a large number of bubbles, resulting in a loose internal structure of the material and greatly improved air permeability. Excessively high air permeability will affect its barrier effect against microorganisms, particles, etc., and cannot meet the expected performance standards of medical and health products.
[0151] Compared with Example 1, the air permeability of the polydioxanone melt-blown nonwoven material prepared in Comparative Example 4 is 400 mm / s, which is significantly higher than that in Example 1. The reason is that: referring to the microstructure test results of the comparative example, the air flow temperature in the air flow drafting step of the comparative example is set too low, resulting in a coarse and uneven fiber diameter, a large gap between fibers, and easier air passage. In the field of medical protection and sanitary products, although the higher air permeability makes air circulation smoother, it will lead to a decrease in filtering performance, and it is impossible to effectively intercept tiny particles and pathogens, and it is impossible to meet the comprehensive performance requirements of medical protective masks, sanitary products, etc.
[0152] In practical applications, the good air permeability of the meltblown nonwoven material of the present invention can further enhance its practicality in the above-mentioned medical and sanitary products, as well as in the field of medical protection products. In the field of medical protection, the appropriate air permeability ensures that products such as masks and protective clothing can not only effectively block harmful substances such as bacteria and viruses, but also allow users to breathe smoothly, improve wearing comfort and compliance, and reduce protection loopholes caused by discomfort. In the field of sanitary products, sanitary napkins, diapers and other products have good air permeability, which can effectively reduce moisture accumulation, reduce the discomfort and disease risks caused by moisture on the skin, and provide users with a dry and comfortable use experience. In addition, in industrial scenes such as food processing workshops and pharmaceutical workshops that have strict requirements on sanitary conditions, work clothes, air filtration equipment, etc. made of this material can also play a good dual role of air permeability and filtration to ensure the sanitation and safety of the production environment.
[0153] (VI) Application environment simulation test:
[0154] The meltblown nonwoven materials prepared by Examples 1 to 9 were placed in different application environments for simulation tests. Specifically, each meltblown nonwoven material was placed in 30% RH, 60% RH, and 90% RH humidity environments, maintained at 25°C, and placed for 72 hours; each meltblown nonwoven material was immersed in 75% alcohol and iodine for 2 hours, and the immersion process was carried out at 25°C; the tensile strength and elongation at break of the materials after treatment in different simulated environments were tested, and the specific test results are shown in Table 6.
[0155] Table 6:
[0156]
[0157] From the test results in Table 6, it can be seen that under different humidity environments, the tensile strength of the material remains high at 30% RH, but the flexibility of the molecular chain is limited due to the low moisture content, and the elongation at break is reduced; at 60% RH, the absorption of moisture causes the tensile strength to decrease and the elongation at break to increase; at 90% RH, a large amount of water absorption causes a significant decrease in tensile strength and a significant increase in elongation at break; polydioxanone itself has good chemical stability and has a certain tolerance to alcohol and iodine. After alcohol immersion, the tensile strength decreases slightly. Alcohol has certain solubility and permeability, and can penetrate into the material, destroying the entanglement and bonding between fibers, making the structure of the material loose, thereby reducing its strength. On the other hand, the penetration of alcohol causes the fiber to undergo plastic deformation when stretched, thereby increasing the elongation at break, but the increase is limited. After iodine immersion, the solvent swells to slightly reduce the tensile strength, and the elongation at break may not change much or increase slightly due to the small swelling and insignificant damage.
Claims
1. A method for preparing a polydioxanone degradable melt-blown nonwoven material, characterized in that: The invention uses polydioxanone as a raw material, heats and melts it in a twin-screw extruder, extrude it from a spinneret, and draw it at high speed in a hot air flow to form fibers, which are then collected by a receiving device through self-adhesion into a web; wherein the viscosity of polydioxanone is 1.5 dL / g-2 dL / g, and the melt index is 20 g / 10 min-25 g / 10 min; in the heating and melting step, the temperature of the twin-screw extruder is set to 85°C-95°C in the first zone, 155°C-165°C in the second zone, 170°C-180°C in the third zone, 170°C-180°C in the fourth zone, and 170°C-180°C in the die head; in the air flow drawing and forming step, the aspect ratio of the spinneret is (10-20):1, the air flow pressure is 0.1 MPa-0.5 MPa, and the air flow temperature is 160°C-180°C.
2. The method for preparing the polydioxanone degradable melt-blown nonwoven material according to claim 1, characterized in that: The raw material is polydioxanone slices, which are dried by vacuum heating; wherein the vacuum heating drying conditions are: the drying temperature is set at 50° C. to 70° C., and the drying time is 12 hours to 48 hours.
3. A polydioxanone degradable melt-blown nonwoven material prepared by the preparation method as described in any one of claims 1 or 2.
4. An application of the polydioxanone degradable melt-blown nonwoven material as claimed in claim 3, characterized in that: In the field of clinical medicine, it is used as a material for surgical dressings, wound bandages, masks, and protective clothing; in the field of sanitary materials, it is used as a material for sanitary napkins, diapers, and wet wipes.
5. An application of the polydioxanone degradable melt-blown nonwoven material as claimed in claim 3, characterized in that: In the agricultural field, it is used as a material for making plant covering cloth and seed coating.
6. An application of the polydioxanone degradable melt-blown nonwoven material as claimed in claim 3, characterized in that: In the field of food packaging, it is used as a material for making food fresh-keeping packaging.
Citation Information
Patent Citations
Medicinal gullet scaffold fiber and preparation method thereof
CN102071491A
Segmented, epsilon-caprolactone-rich, poly(epsilon-caprolactone-co-p-dioxanone) copolymers for medical applications and devices therefrom
CN104066459A
Poly (p-dioxanone) / polyvinyl alcohol hydrogel and preparation method thereof
CN115895155A
Small diameter metal tube punching processing device and small diameter metal tube punching processing method
KR102779235B1
Bioabsorbable multilayer nasal valve spreader graft
US20120215307A1
Cited By
Fully degradable twin-spun non-woven flexible composite material and preparation method and application thereof
CN120250243A